Pemberdayaan Santri melalui Peningkatan Keterampilan Pengolahan Data dengan Microsoft Excel - Rizayanti; Nindian Sari (PASAI : Jurnal Pengabdian kepada Masyarakat, 2024)
The empowerment of santri at Dayah Bustanul Muhtadin aims to enhance their skills in data processing using Microsoft Excel, a crucial tool in today’s digital era. This skill is not only relevant in education but also in professional and managerial settings within the pesantren. The training program was conducted in several stages, including preparation, training, evaluation, and follow-up. The training began with an introduction to basic Excel usage, followed by lessons on formulas, charts, pivot tables, and Excel applications in pesantren administration. Evaluation was carried out through practical exams and feedback to assess the santri's understanding and application of skills. Results from the program showed a significant improvement in the santri's ability to use Excel, with over 80% of participants effectively utilizing various features. This skill improvement also positively impacted the efficiency of pesantren administration, such as managing financial data and attendance records. The program is expected to provide the santri with valuable digital skills, contributing to improved managerial quality within the pesantren. Overall, this initiative successfully empowered the santri and prepared them to face challenges in the digital and professional world.